AGENDA PÓS-MODERNA E EDUCAÇÃO: INFLUÊNCIAS NAS DIRETRIZES CURRICULARES NACIONAIS GERAIS PARA A EDUCAÇÃO BÁSICA- DCNs/10 - Deitos, Juliano Marcelino (2014)
This research aims to analyze the National General Curriculum Guidelines for Basic Education 2010 - DCNs/10, in order to understand the theoretical foundations, from the formulations and forwards the so call postmodern agenda. It seeks to dialectically apprehend the contradictions and antagonisms in that capital, labor and state relationship, as components of the social metabolism system of the capital, and its influences in relation to the debate called postmodern agenda in education. It seeks to highlight the limits and possibilities of education in historical and dialectical materialist perspective. The study's bibliographic and documentary and takes place from the theoretical contributions of Marx, Engels, Mészáros, Lukács, Lessa, Tonet,Moraes and others. In the first chapter, we seek to clarify the mediations, contradictions and antagonisms present between labor, capital and the state and its impact on education and human development. Seeks to demonstrate the changes in the economic, political, social and educational context, based on productions that discuss content covered in the chapter. From this, we use them for contributions, especially of: Marx, Engels, Mészáros, Lukács, Tonet, Lessa, Gounet, Kuenzer, and Pinto Antunes. The second chapter seeks to highlight pertinent to the debate called postmodern agenda and its relationship to the process of organizing and structuring of capital issues and their influences to the area of educational research in Brazil. To do so, we highlight relevant questions about a possible genesis of discussions about the postmodern elements of its ideological base schedule, and conceptualization. Authors from different theoretical perspectives were used in the study, such as:Anderson, Harvey, Lyotard, Eagleton, Kumar, Freitas, Moraes, Wood, Kaplan and others. In the third chapter, we seek to analyze what influences and foundations of postmodern schedule are present in the National Curriculum Guidelines General for Basic Education 2010 - DCNs/10, which corresponds to the CNE/CEB nº 7/2010e the CNE/CEB nº 4/2010. In this sense, some important points are evident from the proceedings on the formulation of such legislation and analysis of assumptions related to the postmodern present in the documents schedule categories. , Among others, the contributions of Shiroma, Moraes, Evangelista, Gomes, Tonet and others were used. From the analysis, it was possible to identify some influences of postmodern agenda in the National Curriculum Guidelines for General Basic Education - DCNs/10 such as: a) hybridity, volatility and uncertainty; b)multiculturalism and decentralization of the working class; c) the centrality of education in defense of citizenship and democracy. These categories showed that the postmodern schedule is constituted as an ideology closely linked to the need for expanding the capital, made possible through the educational policy constitutes the mediations as an extension of social reproduction.